Low-skilled immigration and the expansion of private schools - Davide Dottori; I-ling Shen (Institute for the Study of Labor (IZA), 2009)
This paper provides a political-economic model to study the impact of low-skilled immigration on the host country's education system, which is characterized by sources of school funding, the average expenditure per pupil, and the type of parents who are more likely to send their children to publicly or privately funded schools. Four main effects of immigration are considered: (1) greater congestion in public schools; (2) a lower average tax base for education funding; (3) reduced wages for low-skilled workers and so more dependence by low-skilled locals on public education; (4) a greater skill premium, which makes it easier for high-skilled locals to afford private education for their children, and hence weakens their support for financing public school. It is found that when the size of low-skilled immigrants is large, the education regime tends to become more segregated with wealthier locals more likely to opt out of the public system into private schools. The fertility differential between high and low-skilled locals increases due to a quantity/quality trade-off. The theoretical predictions are consistent with empirical evidence from both the U.S. census data and the OECD Programme for International Student Assessment (2003).
urn:nbn:de:101:1-20090209166
Keywords: H42; H52; I21; D72; O15; 330; Voting; taxes and subsidies; education; fertility; migration; Migranten; Ungelernte Arbeitskräfte; Fruchtbarkeit; Bildungswesen; Privatschule; Bildungsfinanzierung; Theorie